Study of the Etiology of Acute Respiratory Infections in Children Under 5 Years at the Dr. Agostinho Neto Hospital, Praia, Santiago Island, Cabo Verde - Correia, Wilson; Dorta-Guerra, Roberto; Sanches, Mitza; Almeida Semedo, Carmen de Jesús Borges; Valladares, Basilio; de Pina-Araújo, Isabel Inês M.; Carmelo, Emma (Frontiers in Pediatrics, 2021)
Background: Acute respiratory infections are one of the major causes of morbidity and mortality in children under 5 years in developing countries and are a challenge for the health system of these countries. In Cabo Verde, despite the lack of recent studies, data indicate that it affects thousands of children, being the fourth leading cause of infant mortality in 2013. The aim of this study was to identify and describe the etiological agents associated with acute respiratory tract infections in children under 5 years old, and their associated risk factors, such as clinical symptoms or socio-demographic characteristics. Methods: Naso-pharyngeal samples were collected from children under 5 years attending at Dr. Agostinho Neto Hospital (Praia, Santiago Island, Cabo Verde) with suspected ARI at different time-points during 2019. Samples were analyzed using FilmArray® Respiratory Panel v. 2.0 Plus to identify etiological agents of ARI. A questionnaire with socio-demographic information was also collected for each participant. Data analyses were carried out using the IBM SPSS version 25 (IBM Corporation, Armonk, NY) and R 3.5.1 statistical software. Results: A total of 129 naso-pharyngeal samples were included in the study. Seventeen different etiologic agents of respiratory infections were identified. HRV/EV was the most frequent agent detected, followed by FluA H3 and VRS. Coinfection with two or more pathogens was detected in up to 20 % of positive samples. The results were analyzed in terms of age-group, sex, period of the year and other social and demographic factors. Conclusions: Viruses are the main causative agents of ARI in children <5 years attending at the pediatrics service at the Dr. Agostinho Neto Hospital in Praia city, Santiago Island, Cabo Verde. Some factors are described in this study as statistically associated with the presence of an infectious agent, such as having one or more children sharing the bedroom with an adult and the presence of some clinical symptoms. The data addresses the need for studies on respiratory tract infections in Cabo Verde.